Pendampingan Pada Masyarakat Dalam Peningkatan Pendapatan Melalui Program Bazar Ramadhan Di Desa Laweyan - Rona Octavia Mawaddah; Yanda Bara Kusuma (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
In the entrepreneurship program, students focus on entrepreneurship or MSMEs where KKNT activities take place. The goals set by students in this service are that the community can develop their business in a more modern, efficient and inclusive way, giving students experience of integration with the environment, serving the community directly, finding various issues and learning to deal with problems faced by the community. The method of implementing community service activities is a qualitative approach with the type of observation, and distributing pamphlets through social media. Bazaar as a marketing channel and product marketing tool introduces consumers to MSME partners. This was achieved through the collaboration of KKN-T students and MSME partners in holding bazaars. This time, in holding the bazaar, MSME players who attend must be able to attract their own consumers. Of course KKN-T students also help market MSME products. The bazaar event is also expected to increase the creativity of students and MSME actors in marketing their products. By holding the Ramadhan Bazaar in Laweyan village, it can increase the income of MSME players and expand the existing market share. In addition, MSME actors have started to create social media accounts and promote their products and are willing to create NIBs to make business easier. About 90% of MSME partners are satisfied with holding the Ramadhan bazaar and find it helpful. This proves that the cooperation of the committee with the existence of a bazaar in Laweyan village helps as well as prospers the goals of the Thematic KKN entrepreneurship scheme.